2008
DOI: 10.1896/044.015.0211
|View full text |Cite
|
Sign up to set email alerts
|

Densidad poblacional y tamaño de grupo de <i>Saguinus leucopus</i> en parches de bosque en el departamento de Caldas, Colombia

Abstract: No abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
1
6
0
3
Order By: Relevance
“…The habitat use of C. thous has always been associated with forest environments in the literature, but it is noted that it also exhibits flexibility due to its use of open areas. On the other hand, Lycalopex gymnocercus is more strongly associated with open areas (Langguth, 1975;Redford and Eisenberg, 1992;Sánchez-Lalinde and Pérez-Torres, 2008). Our results showed that both canids used the three habitat types differentially, supporting the information in the literature.…”
Section: Discussionsupporting
confidence: 85%
“…The habitat use of C. thous has always been associated with forest environments in the literature, but it is noted that it also exhibits flexibility due to its use of open areas. On the other hand, Lycalopex gymnocercus is more strongly associated with open areas (Langguth, 1975;Redford and Eisenberg, 1992;Sánchez-Lalinde and Pérez-Torres, 2008). Our results showed that both canids used the three habitat types differentially, supporting the information in the literature.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, they explained that their proposal must be understood as a provisional classification that includes some heuristic or instrumental value, but that needs to be tested and is open to rectification. Despite this, these units have been broadly employed by researchers, planners, and governmental entities to create policies of land use and conservation areas (Henao-Sarminento et al 2008;Latorre et al 2014;Colombia 2012;Rámirez-Chaves et al 2013;Roncancio et al 2011;Solar et al 2013). As Hernández-Camacho et al (1992) points out, these biogeographic units must be tested before employing them.…”
Section: Discussionmentioning
confidence: 99%
“…), White‐footed tamarins are only found in one protected area, the Parque Nacional Natural Selva de Florencía. Unfortunately the importance of this protected area for the conservation of the species is very small because only a small proportion of the park is within the altitudinal range of the species (Roncancio et al ., ). There are some regional protected areas where the species has been reported but the populations within these areas have not been studied and, thus, the effectiveness of these areas and their relative contribution to the conservation of the species are unknown (N. Roncancio, pers.…”
Section: Introductionmentioning
confidence: 97%
“…comm.). Although some studies have been carried out, relatively little is known about the biology of this primate and its response to the reduction, degradation and fragmentation of forests (Roncancio et al ., ).…”
Section: Introductionmentioning
confidence: 97%